Multiobjective Programming and Goal Programming Theoretical Results and Practical Applications - Barichard, Vincent; Ehrgott, Matthias; Gandibleux, Xavier; T'Kindt, Vincent; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book gives the reader an insight into the state of the art in the field of multiobjective (linear, nonlinear and combinatorial) programming, goal programming and multiobjective metaheuristics. The 26 papers describe all relevant trends in this fields of research . They cover a wide range of topics ranging from theoretical investigations to algorithms, dealing with uncertainty, and applications to real world problems such as engineering design, water distribution systems and portfolio selection. The book is based on the papers of the seventh international conference on multiple objective programming and goal programming (MOPGP06).
Multiobjective Programming and Goal-Programming -- A Constraint Method in Nonlinear Multi-Objective Optimization -- The Attainment of the Solution of the Dual Program in Vertices for Vectorial Linear Programs -- Optimality of the Methods for Approximating the Feasible Criterion Set in the Convex Case -- Introducing Nonpolyhedral Cones to Multiobjective Programming -- A GP Formulation for Aggregating Preferences with Interval Assessments -- Multiobjective Combinatorial Optimization -- Bicriterion Shortest Paths in Stochastic Time-Dependent Networks -- Clusters of Non-dominated Solutions in Multiobjective Combinatorial Optimization: An Experimental Analysis -- Computational Results for Four Exact Methods to Solve the Three-Objective Assignment Problem -- Constraint Optimization Techniques for Exact Multi-Objective Optimization -- Outer Branching: How to Optimize under Partial Orders? -- Multiobjective Metheuristics -- On Utilizing Infeasibility in Multiobjective Evolutionary Algorithms -- The Effect of Initial Population Sampling on the Convergence of Multi-Objective Genetic Algorithms -- Pattern Mining for Historical Data Analysis by Using MOEA -- Multiple-Objective Genetic Algorithm Using the Multiple Criteria Decision Making Method TOPSIS -- Multiobjective Games and Uncertainty -- Multi-Criteria Simple Games -- Multiobjective Cooperative Games with Restrictions on Coalitions -- An Experimental Investigation of the Optimal Selection Problem with Two Decision Makers -- Solving a Fuzzy Multiobjective Linear Programming Problem Through the Value and the Ambiguity of Fuzzy Numbers -- A Robust-Solution-Based Methodology to Solve Multiple-Objective Problems with Uncertainty -- Interactive Methods and Applications -- On the Use of Preferential Weights in Interactive Reference Point Based Methods -- Interactive Multiobjective Optimization of Superstructure SMB Processes -- Scheduling of Water Distribution Systems using a Multiobjective Approach -- On Conditional Value-at-Risk Based Goal Programming Portfolio Selection Procedure -- Optimal Bed Allocation in Hospitals -- Multiobjective (Combinatorial) Optimisation$1 (BSome Thoughts on Applications -- Multi-scenario Multi-objective Optimization with Applications in Engineering Design.s
Keywords: Business; Operations research; Decision making; Computer simulation; Mathematical optimization; Engineering; Computational intelligence; Economic theory; Business and Management; Operation Research/Decision Theory; Engineering, general; Optimization; Simulation and Modeling; Economic Theory/Quantitative Economics/Mathematical Methods; Computational Intelligence; Electronic books